Contribution of Islamic Law to the Draft Law on the Elimination of Sexual Violence - Huda, Muhammad Wahyu Saiful; Astrovanapoe, Syahlila Umaya (Jurnal Scientia Indonesia, 2021)
Cases of sexual violence are like an iceberg. Whereas human rights in the constitution have been contained, and mandated protection for the people of Indonesia. Especially with the Covid-19 pandemic, cases of sexual violence in Indonesia have increased drastically. In Indonesia's positive law has also contained love and obscenity. However, this still does not cover all the problems or types of sexual violence that occur. To cover all aspects of violence, Komnas Perempuan formed a bill on the Elimination of Violence. This bill is expected to examine the existing laws in Indonesia so far. Assessing that the majority of the Indonesian population is Muslim. So, the contents of the bill must not conflict with Islamic law. The research method used is normative juridical. With data sourced from literature on the internet. The PKS Bill is very urgent to ensure the safety of victims and other weak people who have the potential to become victims of sexual violence. However, this bill contains elements of sexual violence in the domestic sphere where a husband who forces him to have sex will be threatened with a crime. It should be noted, this coercion on what basis. The reason why the wife according to Islamic law must be clear according to the rules. During menstruation or when you are sick, it is permissible to refuse.